Mediation as A Choice of Medical Dispute Settlements in Positive Law of Indonesia - Mohammad Irfan (Fakultas Hukum, Universitas Warmadewa, 2019)
The aims of this research to see how the pattern of mediation is seen as effective in resolving medical disputes in the review of Law No. 30 of 1999 concerning Arbitration and alternative resolutions of off-court disputes and Perma No. 1 of 2016 concerning Mediation in the court. The research methodology used is the Normative legal research methodology with a document study approach/literature study, by examining references related to the writing object. Based on the results of the study in the case of cases of medical disputes or disputes between patients and doctors/dentists and/or hospitals including those who feel disadvantaged by the actions of doctors/dentists in accordance with Article 66 of Law No. 29 of 2004 concerning Medical Practice, better resolved by mediation In mediation, the parties directly discuss what is the process of resolving disputes that are discussed and voluntary and provide information on what might offer a chronological and expected approach in overcoming demands, preferably mediation used as the main form in resolving medical disputes, because mediation is faster, cheaper, easier, and its nature does not cause long hostilities because no one is defeated